CAD of Antenna Feed Systems With Tracking Capabilities by Controlling High Order Modes - Juan Luis Cano; Gabriele Ceccato; Luca Perregrini (IEEE Access)
This work presents a workflow to simplify the design process, simulation effort and verification scheme, to generate a signal with desired power, polarization and controlled higher-order modes required for aeronautical tracking systems. This workflow is especially suitable for the simulation and analysis of complex antenna feed systems with multimode monopulse tracking capabilities through the emulation of real operation. The presented scheme is based on S-parameters obtained from literature or full-wave simulations and linear techniques, transforming a CAD-FEM problem into a circuital one, that can be easily implemented analytically and processed in commercial schematic simulation tools. The proposed approach is applied to the analysis of an antenna feed system with a resonant TE21 tracking coupler, commonly used in tracking systems today and can be easily adapted and/or extended to more complex feed systems working with different tracking couplers and/or high-order modes. Different polarizations and feed settings are analyzed, obtaining useful information on the operation and best configuration of these complex systems.